A proteomic approach to decipher chilling response from cold acclimation in pea (Pisum sativum L.) - Dumont, Estelle (Plant science : an international journal of experimental plant biology, 2011)
Copyright © 2010 Elsevier Ireland Ltd. All rights reserved.